Membangun Sekolah sebagai Ruang Dialog: Studi Kasus di SMA Kolese Gonzaga: Establishing School as a Dialogue Space: A Case Study at Kolese Gonzaga High School - Anggi Afriansyah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
Dialogue is an important part of strengthening democratization. However, dialogue has not been fully practiced and prioritized in schools. Schools become important institutions to promote tolerance and dialogue from various traditions or cultural backgrounds. Strengthening dialogue is an important part of the humanist education approach. This research discussed how Kolese Gonzaga High School established a learning system that provides a large space for dialogue. In each activity, the school tries to develop communication skills, learn to understand each other, and also collaborate with various communities. This research focused on two things: (i) the practice of establishing school as a space for dialogue, and (ii) how school can promote dialogue for peace. This research was qualitative research with a case study approach. Informants were selected using a purposive sampling technique. Meanwhile, the data collection techniques used are in-depth interviews, observation, and literature study. Interviews were conducted with school principals, teachers, students, and parents. Dialogue activities are strengthened in various activities at school. Kolese Gonzaga High School establishes dialogue spaces in various fields in the school such as in classrooms, daily activities, and activities outside of school.